2016
DOI: 10.1007/s10930-016-9688-4
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Glutathione Binding to Human Eukaryotic Elongation Factor 1 Gamma: Isothermal Titration Calorimetry and Molecular Dynamics Studies

Abstract: The energetics of ligand binding to human eukaryotic elongation factor 1 gamma (heEF1γ) was investigated using reduced glutathione (GSH), oxidised glutathione (GSSG), glutathione sulfonate and S-hexylglutathione as ligands. The experiments were conducted using isothermal titration calorimetry, and the findings were supported using computational studies. The data show that the binding of these ligands to heEF1γ is enthalpically favourable and entropically driven (except for the binding of GSSG). The full length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…The Gibbs' free energies of the different interactions (DG = ca. À5.6 kcalÁmol À1 ; [29]) are similar to those determined for PcEF1Bc (Table 3). However, contrary to PcEF1Bc, the human protein has slightly lower affinities for GSH than for GSSG (K d of 67 and 115 µM, respectively; [29]) (Table 3).…”
Section: Pcef1bc Efficiently Binds Gssg Leading To Conformational Changes Of the Proteinsupporting
confidence: 83%
See 3 more Smart Citations
“…The Gibbs' free energies of the different interactions (DG = ca. À5.6 kcalÁmol À1 ; [29]) are similar to those determined for PcEF1Bc (Table 3). However, contrary to PcEF1Bc, the human protein has slightly lower affinities for GSH than for GSSG (K d of 67 and 115 µM, respectively; [29]) (Table 3).…”
Section: Pcef1bc Efficiently Binds Gssg Leading To Conformational Changes Of the Proteinsupporting
confidence: 83%
“…À5.6 kcalÁmol À1 ; [29]) are similar to those determined for PcEF1Bc (Table 3). However, contrary to PcEF1Bc, the human protein has slightly lower affinities for GSH than for GSSG (K d of 67 and 115 µM, respectively; [29]) (Table 3). The preference for GSH over GSSG by the full-length heEF1c could indicate that the C-terminal part may structurally influence glutathione binding to heEF1c by hindering the binding of GSSG [29].…”
Section: Pcef1bc Efficiently Binds Gssg Leading To Conformational Changes Of the Proteinsupporting
confidence: 83%
See 2 more Smart Citations
“…In our previous study, we showed that heEF1γ displays affinity for glutathione; hence, heEF1γ was purified by using glutathione‐Agarose affinity chromatography . We also showed that NT‐heEF1γ exhibits ligandin function toward glutathione and analogues of glutathione by using isothermal titration calorimetry . In this study, we observed that NT‐heEF1γ undergoes glutathione‐induced dimerization.…”
Section: Discussionmentioning
confidence: 99%